National Prevalence of Salmonella enterica Serotype Kentucky ST198 with High-Level Resistance to Ciprofloxacin and Extended-Spectrum Cephalosporins in China, 2013 to 2017 - Honghu Chen; Jingjie Song; Xianying Zeng; Dandan Chen; Rongchang Chen; Chen Qiu; Kai Zhou (mSystems, 2021)
ABSTRACT Salmonella enterica serotype Kentucky is frequently associated with high-level fluoroquinolone resistance and has gained epidemiological importance globally. A retrospective screening was performed to understand the national prevalence of ciprofloxacin-resistant S. Kentucky in China. S. enterica strains (n = 15,405) were collected within the frame of two national surveillance networks between 2013 and 2017. Thirty-three S. Kentucky strains were detected in 5 of 10 provinces, and 27 were assigned to sequence type 198 (ST198). The 27 isolates were multidrug resistant, with high-level resistance to ciprofloxacin, and 21 isolates were further resistant to extended-spectrum cephalosporins (ESCs). Phylogenomic analysis classified ST198 isolates into two clades (198.1 and 198.2), and recent occurrences of inter-/intraregion and interhost transmission were identified. Phylogenetic reconstruction with a global collection showed that one subclade of clade 198.2 was clustered with historical strains from Egypt, and the other one was clustered with strains from Southeast Asia. Isolates of clade 198.1 were clustered with strains isolated from North America. The various patterns of mutations detected in quinolone resistance-determining regions of GyrA and ParC are accordant with the phylogenetic structure. These findings indicate that our isolates may have various origins. SGI1 was exclusively detected in isolates of clade 198.2 with a highly mosaic structure, which were mainly identified as SGI1-K derivatives. Plasmid-mediated quinolone resistance genes qnrS1 and aac(6′)-Ib-cr were identified in three isolates, and blaCTX-M-9 and blaCTX-M-27 were detected in 20 of 21 ESC-resistant isolates. This is the first report of the genetic and epidemiological characterization for the S. Kentucky epidemic clone ST198 in China, warranting the necessity of surveillance for the high-risk clone. IMPORTANCE Ciprofloxacin and extended-spectrum cephalosporins are the choice for treatment of severe nontyphoidal S. enterica infections in adults. S. enterica serotype Kentucky ST198 has gained epidemiological importance globally, because the clone is frequently resistant to both of these high-level-resistance drug groups. The genetic and epidemiological characterization of S. Kentucky has been well studied in Western countries; however, the information is unclear for China. To fill in the gap, we here did a retrospective screening on a large collection in China, and ST198 isolates were systematically analyzed by whole-genome sequencing. Our study revealed that multidrug-resistant ST198 has spread in five provinces, and the occurrences of interregion and cross-host clonal disseminations were detected. Of note, phylogenomic analysis suggests that the Chinese isolates may have emerged with diverse origins, including Egypt, Southeast Asia, and North America. This study warrants the necessity of surveillance for the high-risk clone to prevent its further dissemination in China.